Cover Image, Volume 119, Number 7, July 2018. Issue 7 (July 2018) - He, Hui; Li, Wen; Peng, Min; Qin, Jianbing; Shi, Jinhong; Li, Haoming; Tian, Meiling; Zhang, Xinhua; Lv, Guangming; Jin, Guohua
Abstract : Cover : The cover image, by Hui He et al., is based on the Research Article MicroRNA expression profiles of neural stem cells following valproate inducement, DOI:10.1002/jcb.26831 .